The Existence of Surau Tinggi Siulak Panjang as an Islamic Educational Institution in Kerinci (1951-1957) - Azizah, Faras Puji; Hidayat, Ahmad Taufik; Firdaus, Firdaus (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2024)
Islamic Education Institutions in Indonesia grew and developed from surau, pesantren, and dayah, which are the forerunners of Islamic education institutions in Indonesia. Traditional educational institutions called surau were also developed in the Siulak Kerinci area. This is surau as a place to foster the generation of Islamic scholars in Siulak Kerinci. There were several surau in Siulak at that time, but the one that had an Islamic education institution was Surau Tinggi. This research aims to trace the traces of traditional Islamic educational institutions in Siulak that once existed. The method used is the historical method with stages, namely heuristics, criticism, interpretation, and historiography. The results of this study show that from 1935 to 1947, several Siulak people went to study outside Siulak and even outside Kerinci. They returned to their homeland to teach the knowledge gained to the Siulak community in their respective homes. In 1951, an Islamic education institution was established in Surau Tinggi, which was developed by several religious leaders in Siulak, namely H. A Khamis, Mat Serak who came later, Tarmizi, and Mat Run Salim. They succeeded in motivating the community and their friends about the importance of education. Finally, a formal Islamic education institution was established, madrasah (MTI), in 1957 and developed until it changed its name to MTsS Siulak Gedang; this is the first madrasah in the Kerinci homecoming section. From here, the forerunner of changes in Islamic education institutions in Siulak. This needs to be underlined in Siulak. There is a modernization of education, which was formerly surau to madrasah (MTI-MTsS). Lembaga Pendidikan Islam di Indonesia tumbuh dan berkembang dari surau, pesantren, dayah yang merupakan cikal bakal lembaga pendidikan Islam di Indonesia. Lembaga pendidikan tradisional yang disebut surau berkembang juga di wilayah Siulak Kerinci. Hal ini surau sebagai tempat membina generasi terpelajar Islam di Siulak Kerinci. Ada beberapa surau di Siulak masa itu, namun yang mempunyai lembaga pendidikan Islam yaitu Surau Tinggi. Tujuan Penelitian ini untuk menelusuri jejak lembaga pendidikan Islam tradisional yang pernah eksis. Metode yang digunakan adalah metode sejarah dengan tahapan yaitu heuristic, kritik sumber, Interpretasi, dan historiografi. Hasil dari penelitian ini dapat menunjukkan, bahwa tahun 1935-1947 terdapat beberapa masyarakat Siulak pergi menuntut ilmu ke luar Siulak bahkan keluar Kerinci. Dan kembali ke tanah kelahiran mengajarkan ilmu yang diperoleh kepada masyarakat Siulak yang bertempat di rumahnya masing-masing. Pada tahun 1951 didirikan lembaga pendidikan Islam di Surau Tinggi, yang dikembangkan oleh beberapa tokoh agama di Siulak, yaitu H. A Khamis, Mat Serak yang datang belakangan itu Tarmizi, dan Mat Run Salim. Mereka berhasil memotivasi masyarakat dan teman-temannya bahwa pentingnya pendidikan. Dan akhirnya didirikan lembaga pendidikan Islam formal madrasah (MTI) tahun 1957 dan berkembang sampai berubah nama menjadi MTsS Siulak Gedang, inilah madrasah pertama di bagian Kerinci mudik. Dari sinilah, cikal bakal terjadi perubahan lembaga pendidikan Islam di Siulak. Hal ini perlu digaris bawahi di Siulak ada modernisasi pendidikan yang dahulunya surau menjadi madrasah (MTI-MTsS).